DESIGNING EDUCATIONAL GAME “MATH MAZE” IN MATHEMATICS FOR GRADE 10th USING UNITY 3D - Melvin Nicholas Armansyah; Deli Deli (CoMBInES - Conference on Management, Business, Innovation, Education and Social Sciences, 2022)
Mathematics is a basic science that is used in everyday life, but so many children find it difficult to understand it at school. Children tend to like playing games rather than learning because games are very exciting and competitive, like wanting to have the highest score from other children. Game addiction is very dangerous, children tend to get emotional easily if they lose while playing games. However, if educational games are designed in such a way that children can play and learn in peace, it is very helpful. In this study, the author designed an educational game called "Math Maze" to help students learn mathematics, especially in the subject of numbers. The research method used in this research is the research and development method. This study aims to develop the “Math Maze” game as a medium for practicing numbers in mathematics and to test the effectiveness of the “Math Maze” game as a learning medium. The participants for this “Math Maze” game design research were students of grade 10th. The development model that the researcher uses in this study is the ADDIE model with the stages of analysis (analysis), design (design), development (development), implementation (implementation), and evaluation (evaluation). By this research, it is hoped that it will make it easier for students to understand number material in mathematics through the “Math Maze” game.